Understanding the factors related to how East and Southeast Asian immigrant youth and families access mental health and substance use services: A scoping review. - Chloe Gao; Lianne L Cho; Avneet Dhillon; Soyeon Kim; Kimberlyn McGrail; Michael R Law; Nadiya Sunderji; Skye Barbic (PLoS ONE)
The objective of the review is to identify factors related to how East and Southeast Asian immigrant youth aged 12-24 and their families access mental health and substance use (MHSU) services. To address how East and Southeast Asian youth and their families access mental health and substance use services, a scoping review was conducted to identify studies in these databases: PubMed, MEDLINE (Ovid), EMBASE (Ovid), PsychINFO, CINAHL, and Sociology Collection. Qualitative content analysis was used to deductively identify themes and was guided by Bronfenbrenner's Ecological Systems Theory, the process-person-context-time (PPCT) model, and the five dimensions of care accessibility (approachability, acceptability, availability and accommodation, appropriateness, affordability). Seventy-three studies met the inclusion criteria. The dimensions of healthcare accessibility shaped the following themes: 1) Acceptability; 2) Appropriateness; 3) Approachability; 4) Availability and Accommodation. Bronfenbrenner's Ecological Systems Theory and the PPCT model informed the development of the following themes: 1) Immediate Environment/Proximal Processes (Familial Factors, Relationships with Peers; 2) Context (School-Based Services/Community Resources, Discrimination, Prevention, Virtual Care); 3) Person (Engagement in Services/Treatment/Research, Self-management); 4) Time (Immigration Status). The study suggests that there is a growing body of research (21 studies) focused on identifying acceptability factors, including Asian cultural values and the model minority stereotype impacting how East and Southeast Asian immigrant youth access MHSU services. This review also highlighted familial factors (16 studies), including family conflict, lack of MHSU literacy, reliance on family as support, and family-based interventions, as factors affecting how East and Southeast Asian immigrant youth access MHSU care. However, the study also highlighted a dearth of research examining how East and Southeast Asian youth with diverse identities access MHSU services. This review emphasizes the factors related to the access to MHSU services by East and Southeast Asian immigrant youth and families while providing insights that will improve cultural safety.